Clinical, electrophysiological, and imaging findings in childhood brachial plexus injury. (7th May 2022) - Portwood, Katherin E.; Albayram, Mehmet S.; Stone, Sarah; Zingariello, Carla D.; Sladky, John T.; Chim, Harvey; Kang, Peter B.
Abstract : Aim: To assess the prognostic capabilities of various diagnostic modalities for childhood brachial plexus injuries (BPIs) and brachial plexus birth injury (BPBI) and postneonatal BPI. Method: In this single‐center retrospective cross‐sectional study, we examined children with BPIs diagnosed or confirmed by electrodiagnostic studies between 2013 and 2020, and compared the prognostic value of various components of the electrophysiologic findings, magnetic resonance imaging (MRI) data, and the Active Movement Scale (AMS). We developed scoring systems for electrodiagnostic studies and MRI findings, including various components of nerve conduction studies and electromyography (EMG) for electrodiagnostic studies. Results: We identified 21 children (10 females and 11 males) aged 8 days to 21 years (mean 8y 6.95mo) who had a total of 30 electrodiagnostic studies, 14 brachial plexus MRI studies, and 10 surgical procedures. Among the diagnostic modalities assessed, brachial plexus MRI scores, EMG denervation scores, and mean total EMG scores were the most valuable in predicting surgical versus non‐surgical outcomes. Correspondingly, a combined MRI/mean total EMG score provided prognostic value. Interpretation: Brachial plexus MRI scores and specific electrodiagnostic scores provide the most accurate prognostic information for children with BPI. Our grading scales can assist a multidisciplinary team in quantifying results of these studies and determining prognosis in this setting. What this paper adds: A new scoring system to quantify results of electrodiagnostic and magnetic resonance imaging (MRI) studies is presented. Severity of denervation has good prognostic value for childhood brachial plexus injuries (BPIs). Composite electromyography scores have good prognostic value for childhood BPIs. Brachial plexus MRI has good prognostic value for childhood BPIs. What this paper adds: A new scoring system to quantify results of electrodiagnostic and magnetic resonance imaging (MRI) studies is presented. Severity of denervation has good prognostic value for childhood brachial plexus injuries (BPIs). Composite electromyography scores have good prognostic value for childhood BPIs. Brachial plexus MRI has good prognostic value for childhood BPIs. Childhood brachial plexus injury can have significant consequences and it is important to determine prognosis so that key decisions such as whether and when to consider surgical options can be made in an informed manner. This study examines the comparative utility of clinical, electrophysiologic, and imaging measures for determining prognosis in this setting. This original article is commented on by Bahm on pages 1186–1187 of this issue.